Urban planning as a trading zone - Mäntysalo, Raine; Balducci, Alessandro (Urban and Landscape Perspectives, 2013)
'Trading zone' is a concept introduced by Peter Galison in his social scientific research on how scientists representing different sub-cultures and paradigms have been able to coordinate their interaction locally. In this book, Italian and Finnish planning researchers extend the use of the concept to different contexts of urban planning and management, where there is a need for new ideas and tools in managing the interaction of different stakeholders. The trading zone concept is approached as a tool in organizing local platforms and support systems for planning participation, knowledge production, decision making and local conflict management. In relation to the former theses of communicative planning theory that stress the ideals of consensus, mutual understanding and universal reason, the 'trading zone approach', outlined in this book, offers a different perspective. It focuses on the potentiality to coordinate locally the interaction of different stakeholders without requiring the deeper sharing of understandings, values and motives between them. Galison's commentary comes in the form of the book's final chapter.